PENGEMBANGAN BUM Desa SEBAGAI INDUSTRI PROMOSI EKSPORT DENGAN PENDEKATAN NEW INSTITUSIONAL DI DESA WINONG PASURUAN PROVINSI JAWA TIMUR - Khumaidi; Agus Prianto (Halu Oleo University, 2023)
The global era has a real impact on village development which must respond to the challenges of globalization so that village governments need to carry out institutional-based economic development and local potential development in the NIE (New Institutional Economic) system. The purpose of this writing is to determine the Development Of Bum Desa As An Export Promotion Industry With A New Institutional Approach in Winong Village, Gempol District, East Java. The research method uses a qualitative descriptive approach and is analyzed interactively. The results of the research show that strengthening the village government system in allocating budgets is a sign that the government is present in the midst of a global competitive system to assess global market failures and accelerate the development of local potential as the embodiment of a global village. It is proven that Winong Village is able to answer these challenges by contributing to community development through business. productive economy.